Rethinking Property Rights, Relations, and Wealth Inequality in the Age of Non-Fungible Tokens - Umut Yertüm (İstanbul İktisat Dergisi)
Blockchain technology and the possibility of its impacts entered the world with the printing of the first Bitcoin block in 2009. Although overshadowed by Bitcoin due to its popularity, blockchain has a potential far beyond Bitcoin. Non-fungible tokens (NFTs) are defined as unique digital assets built on blockchains and constitute one of the most important parts of this potential due to its technological infrastructure. This study aims to compare the reasons for the creation and usage areas of important NFTs that have been actively implemented within the framework of traditional property relations. The information and data in this study were prepared using the literature review method and were obtained through projects’ websites and blockchain browsers. The fact that the blockchain infrastructure does not allow things such as copying or modifying NFTs eliminates the need for a third intermediary or approval mechanism in property relations. This results in thousands of dollars-worth of art, games, physical products, and partnerships paving the way for NFTs to be bought and sold without the need for a third-party approval mechanism such as a notaries or Ted Registry Offices. These NFTs are even traded in decentralized secondary markets like OpenSea and have reached a sales volume of over $20 billion. However, 85% of NFT trades are found to have bene made by thetop 10% wallets. The fact that the vast majority of valuable NFTs are concentrated in a small group reinforces the phenomenon of wealth inequality in blockchain.